(untitled) (Mwanga wa Lugha, 2022)
Kenya Institute of Curriculum Development (K.I.C.D.) is a government organization that is charged with the responsibility of deciding what is taught in Kenyan institutions of learning. They have a broad mandate to oversight curriculum at the level of Pre School, Primary Schools, Secondary Schools and Technical Institutions. In regard to curriculum issues universities both public and private have their own mechanisms which are over sighted by the Commission for Higher Education. The Decisions made by K.I.C.D. in regards to selection of texts that will be used in institutions has a serious ramification in terms of encouraging writing in the said genres or even competence since learners cannot in the first place understand what they have not been exposed to. This paper focuses on the Formal Essay in Kiswahili Language that has not had the advantage of being an examinable literary type in the Kenyan system and also makes a brief reference to the Kiswahili Short Story. The reference to the Kiswahili short story has been made because it was preceded by others in the secondary school curriculum. The effect of excluding a genre in the schools’ curriculum has the effect of enhancing its growth while the effect of excluding a genre results in its stagnation. These decisions have far reaching effects as we shall see in the discussion on this paper.